Magnetic resonance imaging features for the differential diagnosis of local recurrence of bone sarcoma after prosthesis replacement - Le Qin; Qiyuan Bao; Jie Chen; Lianjun Du; Fuhua Yan; Yong Lu; Caixia Fu; Weibin Zhang; Yuhui Shen (Journal of Orthopaedic Translation, 2018)
Objective: To explore the imaging features of local recurrences (LRs) based on magnetic resonance imaging (MRI) after oncological orthopaedic surgery with prosthesis reconstruction. Methods: A total of 78 cases totalling 157 scans were retrospectively reviewed. Patients with nodule/mass-like signals were retrospectively classified into LR, infectious pseudotumour, and asymptomatic pseudotumour according to clinicopathological data. LRs were histologically confirmed, and the patients without recurrences were followed up for at least 2 years. Mass size distribution and radiological characteristics were analysed for differential diagnosis of the LR versus pseudotumour. Results: Thirty-three of 78 cases were positive with nodule/mass-like signal findings on the post-operative MRI images. By analysing the size distribution, we found that masses >2.1 cm (14) were almost attributable (98% specificity) to LRs and mostly (84.6%) timely treated. Contrarily, masses ≤2.1 cm (19) are challenging for differential diagnosis of LRs versus pseudotumour and were undertreated in five of the nine LR cases. MRI characteristics of masses ≤2.1 cm were found to be highly heterogeneous, with solid appearance, adjacent infiltration, and less peritumour oedema being significant indicators for LRs (P＜0.05). Receiver operating characteristic curve showed area under curve of 0.93 for this predictive model. Conclusions: For the post-operative MRI surveillance of oncological orthopaedic surgery with prosthesis reconstruction, a mass larger than 2.1 cm was highly specific for recurrence. When a mass was smaller than 2.1 cm, more solid property, more adjacent tissue infiltration, and less muscular oedema indicated recurrence rather than a benign mass. The translational potential of this article: There has been very little data associated with the post-operative magnetic resonance imaging features indicating recurrence in patients with malignant bone sarcoma after prosthesis replacement. This study could help develop diagnostic features of magnetic resonance imaging for differentiating recurrence from benign changes in these patients after prosthesis replacement. Keywords: Magnetic resonance imaging, Post-operative, Prosthesis, Recurrence